A Clinicopathological Overview of Microalbumin and Creatinine Levels as Early Indicators of Renal Injury in Prolanis Participants with Hypertension and Type 2 Diabetes Mellitus at UPT Puskesmas Pinangsori, Central Tapanuli Regency, North Sumatra, Indonesia - Jebo Martarini Hariandja; Johannes Martupa Lumbantoruan; Kaspari Arnando (The International Journal of Medical Science and Health Research, 2025)
Background: The insidious progression of Chronic Kidney Disease (CKD) secondary to Hypertension (HT) and Type 2 Diabetes Mellitus (T2DM) necessitates early detection through sensitive laboratory markers. Microalbuminuria signifies a breach in the glomerular filtration barrier, while a decline in the estimated Glomerular Filtration Rate (eGFR), derived from serum creatinine, indicates a loss of functional renal mass. This study provides a detailed clinicopathological analysis of these markers in a high-risk primary care cohort in Indonesia. Methods: This descriptive, cross-sectional study analyzed secondary laboratory data from 75 participants in the Chronic Disease Management Program (Prolanis) at UPT Puskesmas Pinangsori. All participants had a diagnosis of HT, T2DM, or both. The core laboratory variables were spot urine microalbumin and serum creatinine. Data were statistically analyzed to describe the prevalence of abnormal findings. eGFR was calculated using the 2021 CKD-EPI creatinine equation. From a laboratory perspective, albuminuria was stratified into normoalbuminuria (<30 mg/L), microalbuminuria (30-300 mg/L), and macroalbuminuria (>300 mg/L). Renal function was staged according to KDIGO guidelines based on eGFR. Results: The cohort of 75 participants was predominantly female (81.3%) with a mean age of 60.5 years (SD ± 9.8). The primary diagnosis was hypertension alone (61.3%). Pathological albuminuria was highly prevalent: 29.3% of participants exhibited microalbuminuria, and 2.7% presented with macroalbuminuria. This indicates that 32% of this high-risk group had evidence of compromised glomerular barrier integrity. The mean serum creatinine was 0.92 mg/dL (SD ± 0.29), with a corresponding mean eGFR of 79.9 mL/min/1.73m² (SD ± 20.4). This average eGFR falls into the KDIGO G2 category (mildly decreased). Notably, 21.3% of participants were classified as Stage G2 and 9.3% as Stage G3a, signifying that over 30% had a quantifiable reduction in filtration function. The combined HT and T2DM group showed the highest burden of pathology, with 45% exhibiting microalbuminuria and the lowest mean eGFR (72.0 mL/min/1.73m²). Conclusion: The laboratory data reveal a significant, yet likely subclinical, burden of early-stage kidney disease in this Prolanis cohort. The high prevalence of microalbuminuria, preceding a severe decline in eGFR, serves as a critical pathophysiological warning. These findings underscore the indispensable role of routine, quantitative laboratory screening in primary care to identify incipient nephropathy and guide aggressive therapeutic interventions to preserve renal function and prevent progression to end-stage renal disease. Keywords : Microalbuminuria, Diabetic Kidney Disease, Hypertension, Early Detection, eGFR, Prolanis.